Load and fatigue monitoring in musicians using an online app: A pilot study - McCrary, J. Matt; Ascenso, Sara; Savvidou, Paola; Schraft, Séverine; McAllister, Lesley; Redding, Emma; Bastepe-Gray, Serap; Altenmüller, Eckart (Frontiers in Psychology, 2022)
Background/aims High occupational injury rates are reported in musicians, with a career prevalence of up to 89%. Fatigue and playing (over)load are identified as key risk factors for musicians’ injuries. Self-report fatigue management strategies in sport have demonstrated preventive effects. A self-report fatigue management tool for musicians was developed based on a Delphi survey of international experts and hosted in an online app. The aims of this study are to evaluate the content validity and uptake of this new tool, and explore associations between collected performance quality, physical/psychological stress, pain, injury and fatigue data. Methods University and professional musicians were asked to provide entries into the online app twice per week for 1–6 months. Entries into the app were designed to take 2–3 min to complete and consisted of the following: 6 questions regarding playing load over the previous 72 h; 5 questions regarding current levels in key physical/psychological stress domains (sleep, recovery, overplaying, pain, fitness); one question self-rating of performance quality over the previous day; one question regarding current musculoskeletal symptoms; a reaction time task to evaluate psychomotor fatigue. Results N = 96 participants provided an average of 2 app entries (range 0–43). Increased playing time, rating of perceived exertion (RPE), and feelings of having to “play too much” were consistently associated with increased self-rated performance quality (p ≤ 0.004; 6.7 <| t |< 2148.5). Increased ratings of feeling fit and recovering well were consistently associated with reduced pain severity (p < 0.001; 3.8 <| t |< 20.4). Pain severity was increased (6.5/10 vs. 2.5/10; p < 0.001) in participants reporting playing-related musculoskeletal disorders (PRMDs; symptoms affecting playing). Conclusion The prospective value of regular individual self-report playing load, stress, and performance data collection in musicians is clear. However, limited uptake of the online fatigue management app piloted in this study indicates that new approaches to the collection of these data are needed to realize their potential impact.